Quantum State Reconstruction of an Intense Polarization Squeezed State - Marquardt, Christoph; Heersink, Joel; Chekhova, Maria V.; Klimov, A. B.; Sánchez-Soto, Luis L.; Andersen, Ulrik Lund; Leuchs, Gerd (Quantum Electronics and Laser Science Conference 2006, 2006)
The first quantum reconstruction of an intense Kerr squeezed state is reported. Taking into account the algebraic properties of the Stokes operators, the Wigner function describing a polarization squeezed state can also be fully reconstructed.<br